A Distribuição espacial do crédito PRONAF no estado do Pará entre 2000 a 2015 - OLIVEIRA, Diego Alves Guimarães de (2022)
The central objective of this work was to characterize the spatial distribution of the National Program of the Family Farming Strengthening (PRONAF) in the state of Pará, for the years 2000, 2005, 2010 and 2015, Provided exclusively by the Banco da Amazônia. Methodologically, employed was the Geographic Information System (SIG), which is characterized as a tool that allows you to make a territorial analysis of the municipalities and Pará mesoregions that benefited from that program. Additionally, because it is to have knowledge of the regions where the funding is being targeted, we used the studies of Economic Ecological Zoning areas (EEZ), from EMBRAPA. The results of this research indicated a PRONAF credit concentration for Pará Southeast and Northeast mesoregions, , though - over the analysis period it was found a better redistribution of resources to other mesoregions (Metropolitan Region of Belém, Southwest, Marajó and Lower Amazon) it nevertheless highlights that situation by inherent characteristics of each middle region, the ones less benefited from resource were: Metropolitan Region of Belém and Marajó.